Removal of heavy metals from electroplating wastewater by membrane - Galaya Srisuwan (Songklanakarin Journal of Science and Technology (SJST), 2002)
This research was to study the treatment of heavy metals in electroplating wastewater using membranes. Two selected membrane types, cellulose acetate microfiltration membrane with pore size 0.2 μm and polysulfone ultrafiltration membrane with MWCO of 30 kDa were used in this study. Synthetic and factory electroplating wastewater were used as the samples. The experiments were performed by chemical precipitating both synthetic and factory wastewater in the first step and membrane filtrating of supernatant at the pressure of 50, 100 and 200 kPa in the second step. The concentration of chromium, copper, nickel and zinc of treated water were compared with standard values given by the Ministry of Industry (MOI), Thailand. The experimental results showed that flux was highest at the pressure of 200 kPa and decreased as the pressure decreased. The rejection was highest at the pressure of 50 kPa and decreased as pressure increased. The results from synthetic wastewater were better than those from factory wastewater. Thecapability of heavy metal removal of microfiltration and ultrafiltration membrane was the same, but microfiltration gave more flux. The heavy metal removal efficiency of microfiltration of synthetic electroplating wastewater of four processes of chromium, copper, nickel and zinc electroplating , each was higher than that from factory wastewater but slightly lower than the removal efficiency obtained from composite synthetic wastewater. The removal efficiency of chromium, copper, nickel and zinc from composite synthetic wastewater was higher than those from composite factory wastewater for both microfiltration and ultrafiltration processes. The results from the study of membrane surface washing showed little flux increase after washing the membrane by stirring with a propeller at a distance of 2 mm above membrane surface at 400 rpm for 30 minutes.